2018
DOI: 10.1007/s10068-018-0450-x
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study on anti-oxidative and anti-inflammatory properties of hydroponic ginseng and soil-cultured ginseng

Abstract: Hydroponic ginseng (HPG) and soil-cultured ginseng (SCG) were extracted in 70% methanol to quantify relative content of 8 ginsenosides and polyphenolic compounds, and flavonoids to compare their antioxidative effects. Level of nitric oxide and inflammatory targets produced in LPS-stimulated RAW 264.7 cells were measured. 2-year-old HPG shoots contained highest levels of ginsenoside Rb2, Rb3, Rd, Re, and F1. Total polyphenol content was highest in shoots of HPG, followed by roots of HPG and SCG. HPG shoots had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Ginseng ( Panax ginseng Meyer, Asian ginseng) has been widely consumed as an herbal medicine because of its efficacy as an anticancer-, antioxidant-, anti-inflammatory, and anti-obesity agent [ 20 ]. The source of these functional merits is related to various compositions of ginsenoside content as well as phenolic and flavonoid compounds [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginseng ( Panax ginseng Meyer, Asian ginseng) has been widely consumed as an herbal medicine because of its efficacy as an anticancer-, antioxidant-, anti-inflammatory, and anti-obesity agent [ 20 ]. The source of these functional merits is related to various compositions of ginsenoside content as well as phenolic and flavonoid compounds [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the total polyphenolic and flavonoid content of soil-cultured ginseng and hydroponic ginseng was measured. While soil-cultured ginseng contained 17.36 mg gallic acid equivalent/g and 1.44 mg kaempferol/g, respectively, hydroponic ginseng had 31.80 mg gallic acid equivalent/g and 2.31 mg kaempferol/g, respectively [ 20 ]. The total phenolic and flavonoid content of hydroponic ginseng was roughly twofold higher than that of soil-cultured ginseng, and these results were consistent with the results of antioxidant analysis shown in Figure 1 and Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the amount of nitric oxide (NO) produced from the RAW 264.7 cells, as a form of NO 2- present in the cell medium, was measured and RT-PCR was performed to measure the expression of iNOS and cytokines, including IL-6, IL-1β, and TNF-α. It has been reported that roots and shoots of hydroponic ginseng, as well as ginseng, exhibit the inhibitory effects of inflammation in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells [2]. To evaluate the anti-inflammatory activity of non-fermented and fermented HPG, cytotoxicity in RAW 264.7 cells was preliminarily assessed using a 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium (MTT) assay.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the management cost of a hydroponic cultivation technique is much less time-consuming and more economical than that of the conventional soil-cultivation technique. Very few studies, comparing the functional effects of HPG to those of ginseng cultivated in soil, exist but some researchers reported anti-oxidative and anti-inflammatory properties of hydroponic ginseng and soil-cultured ginseng [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the fermentation of hydroponic ginseng has been on the rise since 2015. In a previous study, the antioxidant activity and anti-inflammatory effects of fermented hydroponic ginseng was demonstrated [27,28]. Consequently, fermenting hydroponically cultivated ginseng with probiotics, which is known to have better functionality than soil-cultivated ginseng, is considered promising.…”
Section: Neuroprotective Effectmentioning
confidence: 99%